2017
DOI: 10.1016/j.bbr.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Levo-tetrahydropalmatine inhibits the acquisition of ketamine-induced conditioned place preference by regulating the expression of ERK and CREB phosphorylation in rats

Abstract: Levo-tetrahydropalmatine (l-THP) is an alkaloid purified from the Chinese herbs Corydalis and Stephania and has been used in many traditional Chinese herbal preparations for its sedative, analgesic and hypnotic properties. Previous studies demonstrated that l-THP has antagonistic activity on dopamine receptors; thus, it may have potential therapeutic effects on drug abuse. However, whether l-THP affects ketamine-induced conditioned place preference (CPP) remains unclear. Therefore, the present study was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…As a DA receptor antagonist, l - THP has therapeutic potential in the treatment of addiction to many drugs, including cocaine [ 15 ], heroin [ 16 ], and methamphetamine [ 17 ]. In our previous study, l - THP showed a potential therapeutic effect on KET addiction [ 10 ]. However, the pharmacokinetic effects of l - THP on KET remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a DA receptor antagonist, l - THP has therapeutic potential in the treatment of addiction to many drugs, including cocaine [ 15 ], heroin [ 16 ], and methamphetamine [ 17 ]. In our previous study, l - THP showed a potential therapeutic effect on KET addiction [ 10 ]. However, the pharmacokinetic effects of l - THP on KET remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As a nonselective DA antagonist, l - THP has recently emerged as a promising agent for treating addiction to many types of drugs, including cocaine [ 6 , 7 ], methamphetamine [ 8 ], and oxycodone [ 9 ]. In our previous study, l - THP showed a potential therapeutic effect on KET addiction [ 10 ]. Moreover, l - THP is safe and effective, with no obvious side effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that ERKs are involved in the plastic changes induced by the consumption of drugs of abuse ( Radwanska et al, 2005 ). In addition, the inhibition of ERK phosphorylation alters learned place-preference in a paradigm of drug-of-abuse consumption, whereas activation of ERK1/2 is necessary to establish the association between place preference and drug consumption ( Valjent et al, 2006 ; Du et al, 2017 ). In this context, knocking down ERK1 has shown that enhanced ERK2 signaling and repeated exposure to the drug facilitate the plastic changes leading to drug addiction ( Ferguson et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activation of the MAP kinase pathway contributes to the plastic changes induced by drugs of abuse (see; Valjent et al 2004 and references therein). Activation of the MAP kinase pathway is needed for establishing an association between drug consumption and CPP (Valjent et al 2006, Du et al 2017. Of the two predominant ERK isoforms, ERK2 seems more directly involved in remodeling produced by repeated exposure to cocaine.…”
Section: Cocaine Alters Mitogen-activated Protein Kinase (Map) Pathwamentioning
confidence: 99%